Newton-Kantorovich and Smale Uniform Type Convergence Theorem for a Deformed Newton Method in Banach Spaces - Rongfei Lin; Yueqing Zhao; Zdeněk Šmarda; Yasir Khan; Qingbiao Wu (Abstract and Applied Analysis)
Newton-Kantorovich and Smale uniform type of convergence theorem of a deformed Newton method having the third-order convergence is established in a Banach space for solving nonlinear equations. The error estimate is determined to demonstrate the efficiency of our approach. The obtained results are illustrated with three examples.